Pesticides and Ozofractionation: An Investigation to Remove Organic and Inorganic Contaminants from Industrial Wastewater - Fergusson, L. (Asian Journal of Chemistry, 2015)
During the last 50 years, a significant amount of research has been carried out on the treatment of pesticides and industrial wastewater using physico-chemical methods. However, ozofractionation has not been investigated as a means to remove pesticides from wastewater, possibly because it is more typically associated with the treatment of water in aquariums. Therefore, the present study was undertaken to assess the impact of ozofractionation on pesticide-contaminated industrial wastewater. A sample was collected from a storm water holding tank at a pesticide manufacturing site in Australia containing chlorpyrifos, dichlorodiphenyltrichloroethane (DDT), dichlorodiphenyldichloroethylene (DDE), arsenic and zinc. After preliminary analysis, the sample was subjected to ozofractionation and promising results were observed. Chlorpyrifos, DDT, DDE, arsenic and zinc concentrations were 7.2 μg/L, 108 μg/L, 9.5 μg/L, 0.14 mg/L and 0.44 mg/L before treatment and reduced to < 0.5 μg/L, < 2. 0 μg/L, < 0.5 μg/L, 0.01 mg/L and < 0.005 mg/L respectively after treatment. Before treatment, pesticides and metal concentrations were beyond discharge limits, however ozofractionation brought them within the permissible limits set by environmental agencies and processed wastewater could be discharged to an aquatic ecosystem. These findings indicate that ozofractionation may be a useful method for destroying intractable pesticides and removing heavy metals from industrial wastewater.